Lipopolysaccharides from Ralstonia solanacearum induce a broad metabolomic response in Solanum lycopersicum - Zeiss, Dylan R.; Molinaro, Antonio; Steenkamp, Paul A.; Silipo, Alba; Piater, Lizelle A.; Di Lorenzo, Flaviana; Dubery, Ian A. (Frontiers in Molecular Biosciences, 2023)
Ralstonia solanacearum, one of the most destructive crop pathogens worldwide, causes bacterial wilt disease in a wide range of host plants. The major component of the outer membrane of Gram-negative bacteria, lipopolysaccharides (LPS), have been shown to function as elicitors of plant defence leading to the activation of signalling and defence pathways in several plant species. LPS from a R. solanacearum strain virulent on tomato (LPSR.sol.), were purified, chemically characterised and structurally elucidated. The lipid A moiety consisted of tetra-to hexa-acylated bisphosphorylated disaccharide backbone also decorated by aminoarabinose residues in minor species, while the O-polysaccharide chain consisted of either linear tetrasaccharide or branched pentasaccharide repeating units containing α-L-rhamnose, N-acetyl-β-D-glucosamine and β-Lxylose. These properties might be associated with the evasion of host surveillance and aiding the establishment of the infection. Using untargeted metabolomics, the effect of LPSR.sol. elicitation on the metabolome of Solanum lycopersicum leaves was investigated across three incubation time intervals with the application of UHPLC-MS for metabolic profiling. The results revealed the production of oxylipins e.g. trihydroxy octadecenoic acid and trihydroxy octadecadienoic acid, as well as several hydroxycinnamic acid amide derivatives e.g. coumaroyl tyramine and feruloyl tyramine, as phytochemicals that exhibit a positive correlation to LPSR. sol. treatment. Although the chemical properties of these metabolite classes have been studied, the functional roles of these compounds have not been fully elucidated. Overall, the results suggest that the features of the LPSR.sol. chemotype aid in limiting or attenuating the full deployment of small molecular host defenses and contribute to the understanding of the perturbation and reprogramming of host metabolism during biotic immune responses.